2016
DOI: 10.1177/2167479516685579
|View full text |Cite
|
Sign up to set email alerts
|

23 Players, 23 Voices

Abstract: This study’s purpose was to contribute to the understanding of athlete self-presentation on Twitter by focusing on the communication strategies of an entire team of female athletes during an international mega-event, with special attention given to how the athletes’ communication changed in the surrounding time periods. Content analysis was performed on tweets from all 23 players on the U.S. Women’s National Soccer Team during 30-day time periods before, during, and after the 2015 World Cup. Findings revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 37 publications
(125 reference statements)
0
4
0
2
Order By: Relevance
“…Insights into the events were also provided to followers or supporters of the athlete, extending previous professional athlete research (Hambrick et al, 2010) and aligning with event specific research that suggested athletes shared commentary on the events (Clavio et al, 2013;Hayes-Sauder & Blaszka, 2016;Hull, 2014;Kassing & Sanderson, 2010). In addition, athletes in the current study were able to present their followers with images of the competition venue/city revealing similarities to previous research (Hayes -Sauder & Blaszka, 2016;Hull, 2014), while also sharing their thoughts on their preparation and performances during the event. Social media also provided another avenue for athletes to gather information.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Insights into the events were also provided to followers or supporters of the athlete, extending previous professional athlete research (Hambrick et al, 2010) and aligning with event specific research that suggested athletes shared commentary on the events (Clavio et al, 2013;Hayes-Sauder & Blaszka, 2016;Hull, 2014;Kassing & Sanderson, 2010). In addition, athletes in the current study were able to present their followers with images of the competition venue/city revealing similarities to previous research (Hayes -Sauder & Blaszka, 2016;Hull, 2014), while also sharing their thoughts on their preparation and performances during the event. Social media also provided another avenue for athletes to gather information.…”
Section: Discussionmentioning
confidence: 64%
“…Hayes- Sauder & Blaszka, 2016;Hull, 2014;Kassing & Sanderson, 2010). Kassing and Sanderson (2010) examined fan-athlete interaction and relationships during the Giro d'Italia, cycling's tour of Italy, by tracking athletes' posts.…”
Section: Athlete Social Media Use During Sport Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jalkapallon kohdalla tarkastelun kohteena ovat olleet muun muassa USA:n maajoukkueen pelaajien itsensä esittämisen strategiat sosiaalisessa mediassa (Hayes Sauder & Blaszka 2018), minkä lisäksi tutkijat ovat olleet kiinnostuneita esimerkiksi siitä, miten Instagramin käyttäjät ovat kehystäneet yhdysvaltalaisjalkapalloilijoita tiettyjen hashtagien käytön avulla MM-kisojen aikana (Pegoraro et al 2018). Kiinnostava huomio on, että Twitterin itserepresentaatioissa pelaajat päästivät seuraajansa kurkistamaan arvokisojen kulisseihin käsitellessään huomattavan paljon pelikentän ulkopuolisia asioita, kun taas arvokisoihin liittyvillä hashtageilla varustetut Instagram-julkaisujen jaot olivat pääasiassa urheilusuoritukseen liittyviä (Hayes Sauder & Blaszka 2018;Pegoraro et al 2018;ks. myös Turtiainen 2021a).…”
Section: Tutkimusta Urheilijoiden Sosiaalisen Median Käytöstäunclassified
“…Additionally, scholars have investigated how women, specifically, utilize and present themselves on social media. Hayes Sauder and Blaszka’s (2018) study of the 2015 United States Women’s National Team (USWNT) at the Federation Internationale de Football Association (FIFA) Women’s World Cup found that the women were likely to engage in a backstage performance, with notable themes consisting of conversationalist (direct interaction with athletes, celebrities, family and personal friends), informer (general information sharing, like web applications, content, links, and current events), and behind-the-scenes report (candid reports of the person behind the persona such as sightseeing, describing favorite movies, or discussing extracurricular activities). Moreover, Geurin-Eagleman and Burch’s (2016) study of Olympic athletes and their preferred self-presentation style on Instagram furthered the notion that women were more likely to engage in backstage performances (posting about subjects not related to their sport).…”
Section: Motherhood and The Female Athletementioning
confidence: 99%